Smart Reaction Trainer: Development of Technology-Based Reaction Training Tools for Futsal Players - Nur Fitranto; Hendro Wardoyo; Muchtar Hendra Hasibuan; Sri Indah Ihsani; Gusti Andri (Jurnal Segar, 2026)
This study aims to create a technology-based reaction training aid. This tool is called the Smart Reaction Trainer. The research was conducted in Jakarta, while the manufacturing process and trial data collection were carried out at Campus B of the Faculty of Sports and Health Sciences, State University of Jakarta. The method used in this research was the Research and Development method using the ADDIE model development approach (analysis, design, development, implementation, evaluation). The research subjects were futsal players from the State University of Jakarta. The result of the study was the successful creation of a reaction training tool named Smart Reaction Trainer with two reaction time modes, namely 1.5s and 0.7s. The results of the tool trial assessment by futsal players showed that it was highly feasible at 100%, and in terms of attractiveness, 90% rated it very interesting and 10% rated it interesting. The conclusion is that the Smart Reaction Trainer can be used as an alternative training medium that is effective, innovative, and suitable for the needs of modern futsal, and the involvement of technology-based assistive devices greatly helps futsal players in developing their reaction abilities.